A Survey and Typology of Islamic Molded Ware (9th-13th centuries) based on the Discovery of A Potter's Workshop at Medieval Balis, Syria. (15th February 2015) - Mulder, Stephennie
Abstract : Medieval Islamic unglazed molded ware is a common but little-studied type with great potential for use as an interpretive tool in Islamic archaeology. This article presents the current state of knowledge about molded ceramics by organizing and synthesizing the evidence from published sites across the Islamic world and, using the information from these sites, generates a new typology with distinct periodization between the 9th to the 13th century. This typology is then compared with stratigraphically excavated finds from a newly-discovered 13th century molded ceramic workshop at the site of medieval Balis, Syria. Finally, the paper argues that like fine glazed ceramics, molded wares function as carriers of cultural meaning. Because they imitate more expensive luxury items made of metal, molded wares provide tantalizing clues to the taste and consumption patterns of a kind of "middle class" of urban dwellers in medieval Syria.